1996
DOI: 10.1088/0953-8984/8/9/012
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of three- and low-dimensional semiconducting materials with Pb halide and Sn halide units

Abstract: Band-structure calculations, semiempirical as well as ab initio, have been applied to study the electronic band gap of the new exotic natural low-dimensional MX systems (where M = Pb or Sn and X = I, Br or Cl). Moreover, variational calculations are employed to calculate the excitonic binding energies, whose amplification is due not only to the quantum confinement of the excitons but also to a dielectric enhancement effect. A single set of semiempirical parameters is sought to describe the materials; comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
229
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(239 citation statements)
references
References 27 publications
10
229
0
Order By: Relevance
“…Papavassiliou et al reported the value of 3.87 eV for the position of the bandgap of (CH 3 NH 3 ) 4 PbI 6 •2H 2 O by optical absorption spectroscopy. 29 The absence of any feature in the absorption spectrum obtained from the ellipsometry results in Figure 1 combined with the clear assignment of the XRD peaks to The position of the hydrogens on the CH 3 NH 3 + ions and the water is not assigned in (b) and…”
Section: Equationmentioning
confidence: 97%
“…Papavassiliou et al reported the value of 3.87 eV for the position of the bandgap of (CH 3 NH 3 ) 4 PbI 6 •2H 2 O by optical absorption spectroscopy. 29 The absence of any feature in the absorption spectrum obtained from the ellipsometry results in Figure 1 combined with the clear assignment of the XRD peaks to The position of the hydrogens on the CH 3 NH 3 + ions and the water is not assigned in (b) and…”
Section: Equationmentioning
confidence: 97%
“…Theoretical study of Koutselas et al revealed that Eb and energy band gap of hybrid perovskites increases along with the decreasing dimensionality of perovskite. [75] For twodimensional (2D) perovskites, the metal-halide frameworks and the large organic cations are alternated to induce well and barrier electronic structure with different dielectric constants (e.g.…”
Section: Photo-generated Carrier Behaviormentioning
confidence: 99%
“…While it is hard to foresee the E b behavior with increasing dimensionality, in general, E b tends to decrease as well [10]. In most cases it is difficult to obtain crystals of a specific quasi-2D HOIS, especially for n>3, and thus, in such systems the OA and PL spectra appear as being composed as sum of the corresponding spectra of the individual quasi-2D/3D HOIS, see ref.…”
Section: Morphological Properties Of Quasi-2d and 3d Hoismentioning
confidence: 99%
“…HOIS span dimensionalities from 3D to 0D, including intermediate dimensionalities; those between 2D and 3D are designated as quasi-2D. The progress in classical LD semiconductors has given rise to some new types of devices [5][6][7][8][9], where this natural low cost class of LD semiconductors exhibits useful optoelectronic properties [4,[10][11][12][13][14][15] comparable to the artificial class. Examples of such devices are LEDs based on 2D hybrid semiconductors [16][17][18] which function at room temperature, as well as lately reported, LEDs based on 3D hybrid materials [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%